Research on automatic robot charging based on infrared and ultrasonic information fusion. Issue 1 (July 2021) - Hongjie, Yin; Jun, Lu; Qinghe, Zhou; Dong, He
Abstract: In order to realize long-term, continuous, stable and reliable operation of wheeled robot without intervention, the principle of autonomous charging technology is analyzed, and the common and key technologies of wheeled robot autonomous charging are introduced. Aiming at the disadvantages of traditional autonomous charging system. A robot automatic charging docking method based on the combination of infrared radiation sensor, photoelectric tube tracking sensor and ultrasonic distance sensor is adopted. through the data fusion of Kalman filter algorithm for the distance value obtained by ultrasonic sensor, a high precision distance estimation value is obtained, which makes up for the lack of measurement accuracy in traditional infrared method. Experimental tests show that the docking accuracy between robot and charging seat is high. The docking is completed well.